1999
DOI: 10.1046/j.1365-2893.1999.t01-1-6120135.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis viruses in an anti‐human immunodeficiency virus‐positive population from Argentina. Amulticentre study

Abstract: The objectives of this study were to investigate the prevalence of infections with hepatotrophic viruses in an anti-human immunodeficiency virus (HIV)-positive population from Buenos Aires and to compare it among the main risk groups for HIV infection. Four hundred and eighty-four consecutive patients attending the HIV outpatients clinic were studied: 359 men and 125 women, median age 29 years (range 16-67 years); 35.5% had presented acquired immune deficiency syndrome (AIDS)-defining conditions. Two hundred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
4
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 28 publications
7
82
4
4
Order By: Relevance
“…The results of this study indicate that the frequency of HBV markers (38.6%) is similar to that found in other Latin American countries 6,13,20 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of this study indicate that the frequency of HBV markers (38.6%) is similar to that found in other Latin American countries 6,13,20 .…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, the frequency of anti-HCV in HIV patients (0.8%) is much lower than that found in previous reports from Brazil (Santos and São Paulo), Cuba and Argentina, where the seroprevalence of anti-HCV was 36.2%, 17.7%, 15.5%, and 58.5%, respectively 6,7,13,25 . The low frequency found in our study could be explained by the low incidence of intravenous drug use and the infrequent transfusions in this population, which are very different to those reported in the studies cited from Latin America where intravenous drug use 13,18,25 and past history of transfusion 7 were the main risk factors identified for HCV infection in HIV patients.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Taxas mais altas têm sido observadas em estudos de coorte europeus (26,37) . Estudos de prevalência demonstram taxas de co-infecção por VHC-HIV em 4% a 15% entre HSH (6,29) , 60% a 90% entre usuários de drogas injetáveis (8,32,36) e aproximadamente 100% em hemofílicos que receberam concentrados de fatores de coagulação antes da introdução da inativação pelo calor, em 1987 (7,28) . Nos EUA, estima-se que em torno de 30% dos 800 000 indivíduos infectados pelo HIV estejam co-infectados pelo VHC (18,30) .…”
Section: Discussionunclassified
“…Several studies found HIV-positive and AIDS patients to have an increased seroprevalence of anti-HEV IgG compared to those without HIV infection (295)(296)(297). Montella et al-controversially-interpreted their finding of higher HEV seroprevalence in Italian HIV-positive homosexual men than in HIV-negative homosexual men and injection drug users as "[confirmation of] the role of transmission through the fecal-oral route facilitated by sexual practices" (297).…”
Section: Immunosuppression and Impaired Viral Clearancementioning
confidence: 99%